Scotland's Arctic Policy Framework (The Scottish Government, 2019)
For centuries, Scotland and the Arctic have enjoyed close links that have had a lasting impact on our cultural, economic and social fabric. While most visible in our northernmost areas, these bonds are evident across the country and lie at the heart of our valued relationship with Arctic states. Scotland is among the Arctic region’s closest neighbours; we share many features and outlooks and have long looked to each other for inspiration, solutions and ideas.